1986
DOI: 10.1002/j.1556-6676.1986.tb01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Control in Counseling: Intrapersonal Versus Interpersonal Definitions

Abstract: The agreement between two different means of conceptualizing control, the intrapersonal and the interpersonal, were examined in this study. The proportion of topic initiations (intrapersonal definition) and the degree of topic determination (interpersonal definition) were calculated for the client and the counselor for each of 15 time-limited counseling dyads (n = 157). It was found that (a) regardless of which definition of control was used, counselors had more control over the topic than clients; and (b) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Although there are differences in how each system defines control, I view these as less crucial than the method of aggregation. Results of Tracey and Miars (1986) and Tracey (1986a) support this hypothesis. The hypothesized relations among the 15 behavioral control measures are depicted in Figure 1.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Although there are differences in how each system defines control, I view these as less crucial than the method of aggregation. Results of Tracey and Miars (1986) and Tracey (1986a) support this hypothesis. The hypothesized relations among the 15 behavioral control measures are depicted in Figure 1.…”
supporting
confidence: 57%
“…Intrapersonal definitions of control can be viewed as attempts at control, whereas interpersonal control can be viewed as a type of actual control, because the responding participant acquiesces. In a variety of different areas-organizational leadership (Gray, Richardson, & Mayhew, 1968); marriages (Courtright, Millar, & Rogers-Millar, 1979); and counseling (Tracey, 1986a)-little if any correlation has been found between intrapersonal and interpersonal definitions of power. Attempting to exert control by acting in a controlling manner is unrelated to whether one actually achieves control by having the other acquiesce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most central variable in the TI/TF coding scheme is Topic Determination (TD), which is defined as the proportion of topic initiations that are subsequently followed to the total number of topic initiations. This variable reflects an interpersonal definition of control (Tracey, 1986b) and is seen to be indicative of degree of complementarity (Tracey, 1988). A high degree of Topic Determination indicates that most initiated topics are accepted by the other participant, and that there is little relationship conflict over what to discuss.…”
mentioning
confidence: 99%
“…If the participant’s reservations and preliminary negative expectations were confirmed or supported in their initial counseling experience, they reported that they were unlikely to continue to engage in counseling and work with the counselor. Existing literature suggests that a client’s perceptions of the strength of the working alliance in the beginning stages of counseling is related to positive counseling outcomes (e.g., MacFarlane, Anderson, & McClintock, 2015; Principe, Marci, Glick, & Ablon, 2006; Tracey, 1986). For example, in a qualitative study with clients at a university counseling center, MacFarlane et al (2015) found that participants entered counseling with initial misgivings.…”
Section: Discussionmentioning
confidence: 99%